Penerapan Metode Bermain Peran Untuk Meningkatkan Kepercayaan Diri Anak TK DWP 3 Ampelgading Kabupaten Malang - Asmah, Ayu; Resha Rahmadani, Chossy; Muntomimah, Siti (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
This self-confidence is an important foundation for children in facing life's challenges and fostering a strong sense of self-confidence. The problem encountered in this study was low self-confidence in children, as evidenced by their lack of participation in storytelling activities in front of their peers. This study aimed to increase children's self-confidence through the application of role-playing. This study used a Classroom Action Research (CAR) approach and was conducted in two cycles. The subjects were 15 children in Group B at Dharma Wanita Persatuan 3 Kindergarten, Ampelgading. The results of Cycle I were 53.3%. Therefore, in Cycle II, the role-playing topic was changed to